Malignant Peritoneal Mesothelioma in an Infant With Familial ATM Mutations. Issue 8 (November 2018) - Mijalovsky, Analia; Halperin, Daniel; Perez, Yonatan; Zafarov, Beatrice; Shaco-Levy, Ruthy; Kapelushnik, Joseph; Flusser, Hagit; Birk, Ohad S.
Abstract : Ataxia-telangiectasia (A-T), an autosomal recessive disorder characterized by progressive neurologic dysfunction, oculocutaneous telangiectasia, immunodeficiency, and cancer susceptibility, is caused by mutations in the ATM gene. A previous study of 4 A-T patients identified 2 rare homozygous missense mutations residing on the same allele of the ATM gene: c.1514T>C and c.1547T>C, which were shown to decrease ATM levels and increase T-cell acute lymphoblastic leukemia predisposition. We studied 5 patients from 2 consanguineous Bedouin families of the same tribe, presenting with A-T. Whole-exome sequencing data identified the 2 aforementioned mutations in ATM, which segregated within all family members as expected of autosomal recessive heredity. Interestingly, one individual was diagnosed with malignant peritoneal mesothelioma (MPM), an extremely rare neoplasm in pediatric patients. Here, we describe a case of a 4-month-old infant homozygous for the 2 ATM mutations, who developed MPM and died by the age of 2 years. To the best of our knowledge, this is the first case of peritoneal mesothelioma in an infant bearing ATM mutations, and one of the youngest pediatric mesotheliomas described. Thus, the risk of MPM might be considered in the follow-up of A-T patients, and ATM mutations sought in cases of early-onset MPM.